Planar Cell Polarity and E-Cadherin in Tissue-Scale Shape Changes in Drosophila Embryos - Kong, Deqing; Großhans, Jörg (Frontiers in Cell and Developmental Biology, 2020)
Planar cell polarity and anisotropic cell behavior play critical roles in large-scale epithelial morphogenesis, homeostasis, wound repair and regeneration. Cell-Cell communication and mechano-transduction in the second to minute scale mediated by E-cadherin complexes play a central role in the coordination and self-organization of cellular activities, such as junction dynamics, cell shape changes and cell rearrangement. Here we review the current understanding in the interplay of cell polarity and cell dynamics during body axis elongation and dorsal closure in Drosophila embryos with a focus on E-cadherin dynamics in linking cell and tissue polarization and tissue-scale shape changes.